Influence of spousal communication about Family Planning and HIV/AIDS related issues on modern contraceptive use in Nigeria (2017)
Contraceptive use in Nigeria at 15 per cent is low, despite a high human immunodeficiency virus (HIV) prevalence of 3.4 per cent and fertility rate of 5.7 per cent. We assessed the levels of spousal communication on family planning and contraception (FPC) and HIV/acquired immune deficiency syndrome (HIV/AIDS), influence of demographic characteristics on this communication and association between this communication and the respondents’ health behaviours. We used a cross-sectional and nationally representative data on reproductive health and HIV/AIDS-related issues from randomly selected 30,752 men and women of reproductive age. Descriptive statistics, Pearson chi-square (c2 ) and logistic regression were used to analyze the data at 5 per cent significance level. About 61 per cent of the respondents were 25–49 years old and mostly from rural areas (65 per cent). Only 20 per cent of the respondents discussed HIV/AIDS with their spouses within 12 months preceding the survey while 15 per cent discussed FPC. A discussion of both HIV/AIDS and FPC among spouses was reported among 9 per cent compared to 26 per cent who reported discussing either. Respondents aged 35–39 years had higher odds of discussing HIV/AIDS (Odds Ratios [OR] = 7.06:6.16–8.09) than those aged 15–19 years. Urban dwellers also had higher odds (OR = 1.24:1.16–1.31) of HIV/AIDS discussions than rural respondents. Modern contraceptive use was 35 per cent and 23 per cent among respondents who discussed FPC and HIV/AIDS compared to 8 per cent and 9 per cent, respectively, among those who did not. Spousal communication on FP and HIV/AIDS was low and has influenced contraceptive use and HIV positivity in Nigeria. There is a need to encourage spousal discussion on FP and HIV/AIDS, especially among the rural dwellers and the poor and uneducated as a strategy for improving modern contraceptive use.